(untitled) (Tzintzun, Revista de Estudios Históricos, 2024)
The disintegration of the Spanish empire, and the Spanish American independence processes, altered power relations in the Atlantic world, triggering international competition over resources and trade in the American territories of the former Spanish empire. The international scene, then dominated by the monarchies that formed the Holy Alliance –Russia, Prussia, Austria, France–, by Great Britain and by the United States, thus became a major factor in the course and outcome of the conflict between Spain and its former colonial possessions. The aim of this text is to analyze this international context, based on the diplomatic action of world powers, with special emphasis on the United States and England, and evaluate the weight it had in the conflictive informal relations that were established between Spain and the newly independent Mexican nation, between 1821 and 1830.